Integrasi Program Keluarga Harapan (PKH) dalam Perencanaan Pembangunan Daerah Guna Pengentasan Kemiskinan di Kota Tangerang - Siti Dina Setiani; Laeli Nur Khanifah; Dhiya Fathiyyatul Aulia (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
This study aims to analyze the integration of the Family Hope Program (Program Keluarga Harapan/PKH) into regional development planning and its influence on the effectiveness of poverty alleviation in Tangerang City. Urban poverty is characterized by complex and dynamic challenges, requiring integrated, adaptive, and sustainable policy interventions. This research employs a qualitative approach using a descriptive method. Data were collected through interviews, observations, and document analysis, and were systematically analyzed to examine the implementation of PKH within the regional development planning framework. The findings indicate that PKH has become an important instrument in the local poverty reduction strategy; however, its integration into regional development planning documents remains suboptimal. Coordination among government agencies through the Regional Poverty Alleviation Coordination Team (TKPK) has been implemented, although challenges persist in data synchronization, beneficiary data validity, and program implementation. The program has contributed to improving beneficiaries’ access to education and healthcare services. Therefore, strengthening policy integration, improving data management systems, and promoting innovation in regional development planning are essential to enhance the long-term effectiveness and sustainability of poverty alleviation efforts.